Assessment of physicochemical and bacteriological quality of drinking water in Sapele local government area of Delta State, South-South, Nigeria. (27th January 2023) - Edeki, Prince Eseoghene; Isah, Essy Clementina; Mokogwu, Ndubuisi
Abstract: Drinking water quality for human consumption is a global matter of paramount importance. The study aimed to assess the physicochemical and bacteriological quality of drinking water from five major sources in Sapele, Delta State. Using a convenient sampling method, 40 water samples were collected from river, rain, well, borehole, and sachet water sources and examined for physicochemical and bacteriological characteristics. The pH of the water sources examined ranged from 4.5 to 6.8, the total dissolved solids (TDS) ranged between 5 and 14, 000 mg/l, the electrical conductivity (EC) ranged between 10 and 740 μS/cm, and the turbidity ranged between 0.01 and 23.9 NTU. Mean levels of chloride, calcium, iron, lead, copper, and cadmium were below the maximal permissible ceilings based on WHO and NSDWQ standards. The total coliform count ranged between 0 and 9, 000 MN/100 ml, with the mean concentration ranging between 0.001 and 1, 268.13 MPN/100 ml. Water samples from different sources had physicochemical parameters within the stipulated standards, but the biological parameters revealed water sources with contamination. It is recommended that consumers of water from these different sources employ measures to purify their drinking water to forestall potential health risks. HIGHLIGHTS: This study describes the assessment of the quality of drinking water in an urban area in South-South, Nigeria. The study assessed the physicochemical qualities of drinking water quantitatively. The study also assessed the bacteriological qualities of drinking water using quantitative techniques. Several sources of drinking water in the study location were assessed. Local and international standards were employed in the assessment of the drinking water quality. Graphical Abstract